Evaluation of apparent diffusion coefficient and MR volumetry as independent associative factors for extra‐prostatic extension (EPE) in prostatic carcinoma. Issue 3 (25th August 2015) - Lim, Christopher; Flood, Trevor A.; Hakim, Shaheed W.; Shabana, Wael M.; Quon, Jeffrey S.; El‐Khodary, Mohamed; Thornhill, Rebecca E.; El Hallani, Soufiane; Schieda, Nicola
Abstract : Background: To assess mean apparent diffusion coefficient (ADC) and MR‐derived tumor volume (Vt) as associative factors for extra‐prostatic extension (EPE) in prostate cancer (PCa). Methods: With institutional review board approval, 73 consecutive patients diagnosed with PCa at trans‐rectal ultrasound biopsy underwent preoperative multi‐parametric (T2W+DWI+DCE) 3 Tesla MRI before radical prostatectomy between 2012 and 2014; 52% (38/73) patients had EPE. Clinical parameters including: age, prostate serum antigen (PSA), digital rectal examination (DRE) and percentage positive cores (PPC) were recorded. Two blinded radiologists subjectively evaluated for EPE using PI‐RADS with T2W‐MRI. A third blinded radiologist recorded: mean ADC (mm 2 /s) of tumor and tumor volume on ADC and T2W (derived from planar volumetry). VtMAX (the largest volume on ADC or T2W) was documented. Multivariate and receiver operator characteristic analyses were performed. Results: There were no significant differences in age, DRE, or Gleason score between groups ( P = 0.52, 0.06, 0.61, 0.36). PSA approached significance being higher with EPE (12.9 ± 12.6 versus 8.2 ± 7.4; P = 0.06). PPC was higher with EPE (60.9 ± 21.9% versus 38.3 ± 21.6%; P < 0.01) with an area under the curve (AUC) of 0.78 and sensitivity/specificity = 75.7/75% when PPC ≥ 45%. AUC for T2W‐MRI was 0.46–0.51 with sensitivity/specificity = 40.0–42.9/48.6–57.1% (R1, R2). Inter‐observer agreement was fair, k = 0.39. There was no difference in mean ADC between groups (0.89 ± 0.25 versus 0.88 ± 0.19 [EPE] mm 2 /s), P = 0.70. T2W‐Vt, ADC‐Vt, and VtMAX were larger with EPE (5.1 ± 7.4, 5.8 ± 6.5, 6.3 ± 7.4 cm 3 versus 1.6 ± 1.8, 1.8 ± 1.3, 2.1 ± 1.8), P < 0.01. VtMAX AUC was 0.77 with sensitivity/specificity = 78.4/73.5% when VtMAX ≥ 2.1 cm 3 which outperformed all other parameters ( P > 0.05) except PPC ( P = 0.6) for the diagnosis EPE. Conclusion: MR volumetry and percentage of positive core biopsies are associated with EPE; whereas, in this study, other clinical and MR parameters including mean ADC and subjective T2W‐MR analysis were not useful for assessment of EPE. J. MAGN. RESON. IMAGING 2016;43:726–736.